The above graph shows the curves of x 2 and x 3 . Clearly, the line y = 0 is tangent to both the curves. But there exists another such straight line which is tangent to both the curves. Find the equation of the line.
If the line can be represented in the form a x + b y + c = 0 , such that ∣ a ∣ , ∣ b ∣ and ∣ c ∣ are positive integers and g cd ( ∣ a ∣ , ∣ b ∣ , ∣ c ∣ ) = 1 , enter your answer as ∣ a ∣ + ∣ b ∣ + ∣ c ∣ .
Notation : ∣ ⋅ ∣ denotes the absolute value function .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Here's a non-calculus approach: We can find the equation of the desired straight line by solving for their respective polynomial discriminants.
To avoid the abuse of notations, I will define the equation of the straight line that is tangent to both the curves as y = A x + B , where ( A , B ) = ( 0 , 0 ) .
Hence, both the equations { x 2 = A x + B x 3 = A x + B has exactly one real root because there is only one intersection point.
Because there's only one real solution, the quadratic discriminant of the quadratic equation x 2 = A x + B must be equal to 0:
( − A ) 2 − 4 ( 1 ) ( − B ) = 0 ⇔ B = 4 A 2
Similarly, the cubic discriminant of the cubic equation x 3 = A x + B ⇒ x 3 − A x − 4 A 2 = 0 must be 0:
⇒ ⇒ ⇒ ( 0 2 ) ( − A ) − 4 ( 1 ) ( − A ) 3 − 4 ( 0 ) 3 ( − 4 A 2 ) − 2 7 ( 1 ) 2 ( − 4 A 2 ) 2 + 1 8 ( 1 ) ( 0 ) ( − A ) ( − 4 A 2 ) = 0 4 A 3 + 1 6 2 7 A 4 = 0 A = − 2 7 6 4 , 0 ( A , B ) = ( − 2 7 6 4 , 7 2 9 1 0 2 4 ) , ( 0 , 0 )
But since we're looking for a straight line other than y = 0 , then ( A , B ) = ( 0 , 0 ) as stated above. Hence ( A , B ) = ( − 2 7 6 4 , 7 2 9 1 0 2 4 ) only. And so the desired equation is
y = − 2 7 6 4 x + 7 2 9 1 0 2 4 ⇔ 7 2 9 y − 1 7 2 8 x + 1 0 2 4 = 0
with the answer ∣ 7 2 9 ∣ + ∣ − 1 7 2 8 ∣ + ∣ 1 0 2 4 ∣ = 3 4 8 1 .
Nice approach! (+1)
Let f ( x ) = x 2 and g ( x ) = x 3
d x d ( f ( x ) ) ∣ x = a = 2 a and d x d ( g ( x ) ) ∣ x = b = 3 b 2
Since both functions have a common tangent ⟹ 2 a = 3 b 2 ⟹ a = 2 3 b 2
Let A : ( 2 3 b 2 , 4 9 b 4 ) B : ( b , b 3 )
slope m = 3 b 2 = 2 1 b 2 ( 3 b − 2 9 b − 4 )
b = 0 ⟹ 9 b − 4 = 1 8 b − 1 2 ⟹ b = 9 8 ⟹ a = 2 7 8 ⟹ m = 2 7 6 4
Using B : ( 9 8 , 7 2 9 5 1 2 ) ⟹ 1 7 2 8 x − 7 2 9 y − 1 0 2 4 = 0 where, a = 1 7 2 8 , b = − 7 2 9 , c = − 1 0 2 4 and ( ∣ a ∣ , ∣ b ∣ , ∣ c ∣ ) = 1 ⟹ ∣ a ∣ + ∣ b ∣ + ∣ c ∣ = 3 4 8 1
In the second last line, it should be − 7 2 9 y
Problem Loading...
Note Loading...
Set Loading...
Let us say that the common tangent line is tangent to x 2 at ( a , a 2 ) and to x 3 at ( b , b 3 ) . Then by definition of the derivative,
Slope of line tangent to x 2 at x = a ⟹ 2 a .
Slope of line tangent to x 3 at x = b ⟹ 3 a 2 .
Therefore the tangent line of x 2 is ⟹ x − a y − a 2 = 2 a ⟹ y − 2 a x + a 2 = 0 , and that of x 3 is ⟹ x − b y − b 3 = 3 b 2 ⟹ y − 3 b 2 x + 2 b 3 = 0 .
Clearly, these lines must be the same if they are tangent to both the curves. Hence, comparing the lines:
⟹ 2 a = 3 b 2 , ⟹ a 2 = 2 b 3 .
Solving the set of equations, we have two values of b = 0 , 9 8 . Substituting b = 0 in the tangent line of x 3 gives y = 0 (As I had stated before) and b = 9 8 gives 7 2 9 y − 1 7 2 8 x + 1 0 2 4 = 0 , which is the required tangent line equation.
Hence, ∣ a ∣ + ∣ b ∣ + ∣ c ∣ = ∣ 7 2 9 ∣ + ∣ − 1 7 2 8 ∣ + ∣ 1 0 2 4 ∣ = 3 4 8 1